ASOCIALS: RACE, EXCLUIDING AND ABNORMALITY IN THE STATE CONSTRUCTION IN CHILE, 1920-1960. - Fernández Labbé, Marcos (Revista de Historia Social y de las Mentalidades, 2013)
This article proposes a historical  reconstruction of the institutional and  discursive procesess through which the  notion of asocial was articulated by the  Chilean state in the early 20th century.  Working on police, Law and penal  sciences documentation, I explore the  projects aiming to produce a familiarity  with the dangerousness of a wide range of  “undesirable” subjects: prostitutes, repeated  criminal offenders, immigrants, vagrants,  alcoholics and drug addicts. Finally, the  article characterizes the opposition between  social and antisocial practices as a particular  mechanism of state building
Keywords: Social Exclusion; State Building; Social History; 20th century